2013
DOI: 10.1074/jbc.m113.483016
|View full text |Cite
|
Sign up to set email alerts
|

Kindlin Binds Migfilin Tandem LIM Domains and Regulates Migfilin Focal Adhesion Localization and Recruitment Dynamics

Abstract: Background: Migfilin is a focal adhesion protein implicated in control of integrin-mediated cell adhesion, spreading, and migration. Results: Migfilin LIM domains are required for focal adhesion targeting and for binding to kindlin-1 and kindlin-2. Conclusion: Kindlins support migfilin recruitment to focal adhesions and kindlin is important for normal migfilin dynamics in cells. Significance: Migfilin/kindlin interactions are important for regulating subcellular localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 41 publications
2
34
1
Order By: Relevance
“…As kindlin-2 binds ILK more efficiently than kindlin-3 does, we aimed to test whether knocking down endogenous kindlin-2 in NIH3T3 fibroblasts (Brahme et al, 2013) would permit GFPkindlin-3 localization in FAs. Our knockdown fibroblasts exhibited only ,15% residual kindlin-2 (Fig.…”
Section: Ilk Binding Aids Kindlin-2 Fa Targetingmentioning
confidence: 99%
See 2 more Smart Citations
“…As kindlin-2 binds ILK more efficiently than kindlin-3 does, we aimed to test whether knocking down endogenous kindlin-2 in NIH3T3 fibroblasts (Brahme et al, 2013) would permit GFPkindlin-3 localization in FAs. Our knockdown fibroblasts exhibited only ,15% residual kindlin-2 (Fig.…”
Section: Ilk Binding Aids Kindlin-2 Fa Targetingmentioning
confidence: 99%
“…Although all three kindlins play key roles in integrin activation, isoform-specific differences in activation have also been described . We therefore compared kindlin-2 and -3 rescue of a5b1 activation in kindlin-2-knockdown NIH3T3 fibroblasts (Brahme et al, 2013). The ability of integrins to bind soluble ligand provides a widely used functional readout of integrin activation (Bouaouina et al, 2012b;Calderwood, 2004b).…”
Section: Ilk Binding Is Important For Kindlin-2-mediated B1 Integrin mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to β-integrins, multiple kindlin binding proteins (KBPs) have been identified, such as migfilin for kindlin-1 and kindlin-2 (Brahme et al, 2013;Tu et al, 2003), Src and F-actin for kindlin-2 (Bledzka et al, 2016;Liu et al, 2015;Qu et al, 2014), and RACK1 for kindlin-3 (Feng et al, 2012). It has been shown that these KBPs are involved in regulating integrin-mediated cell adhesion and spreading (outside-in signaling), but not integrin activation (insideout signaling).…”
Section: Introductionmentioning
confidence: 99%
“…The protein product of FERMT1 is KIND1, a key intracellular component of focal adhesions, which tightly connects cells to the extracellular matrix. Focal adhesions contain clusters of transmembrane integrin adhesion receptors and intracellular proteins that link integrins to the actin cytoskeleton and to signaling pathways (Brahme et al 2013). Therefore, it is possible that molecular defects in the basement membrane could weaken the attachment of junctional epithelium to tooth surfaces, which could increase the susceptibility of a patient to periodontal disease (Wiebe and Larjava 1998).…”
mentioning
confidence: 99%